Towards Sustainable Innovation A five step approach to sustainable change - Pastoors, Sven (Tectum Wissenschaftsverlag, 2017)
With sustainability having gained a lot of momentum over the last years and companies implementing strategies to create corporate sustainability, there are lots of opportunities for innovation. Thus, the two concepts of sustainability and innovation should not be considered separately - they are closely interlinked with one another. The main goal of sustainable innovation is to develop new products and technologies that have a positive impact on the company's triple-bottom-line. To meet this aim, they have to be ecologically and economically beneficial as well as socially balanced.In order to help companies to improve their sustainable innovation process practically, this book is structured into five possible phases of a sustainable innovation process:Awareness of a sustainability problemIdentification & Definition of the problemIdeation & Evaluation of the solutionsTesting & Enrichment of the solutionsImplementation of the solutions & Green Marketing